À la recherche de la preuve perdue: a simple proof of the Ficken theorem - Dariusz Cichoń (Annales Universitatis Paedagogicae Cracoviensis: Studia Mathematica, 2014)
A new proof of the Ficken criterion is given together with a comment concerning the known proofs and related results.